PERAN KOMUNIKASI DALAM FUNGSI MANAJEMEN PADA PT. ASTRA INTERNATIONAL-HONDA TBK PLAJU PALEMBANG - Sri Porwani (Orasi Bisnis : Jurnal Ilmiah Administrasi Niaga, 2014)
This study was conducted to determine the role of communication to management functions inthe PT. Astra International - Honda Tbk Plaju Palembang. Data were obtained from questionnaires and observation. The sampling technique used was a saturated sampling technique, it was used because of the number of population is less than 30 (thirty) people, where the total population was 11 (eleven) employees in the finance division. the results of this study indicate that the role of the communications to planning function in PT. Astra International-Honda Tbk Plaju Palembang has been performing well; the role of communication to organizing function as a regulatory function in which the management has authority to control all information related to employees and to make company’s rule; The role of communication to the direction function is a function of persuasion in constructing coordination, integration and synchronization. Therefore, the process of employees’ actualization can be implemented well; the role of communication to the supervisory function is as a solution to the internal conflict settlement; Suggestions given is as a company working in the field of sales and service, PT Astra International - Honda Tbk Plaju Palembang should improve the communication skills of all employees, both internal and external communications in order to achieve company goals.